1987
DOI: 10.1111/j.1365-2141.1987.tb04150.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a new antithrombin III familial variant (AT Dublin) with possible increased frequency in children with cancer

Abstract: The antithrombin III (ATIII) isoform pattern of a number of serum and plasma samples was analysed by isoelectric focusing and immuno-blotting. A novel ATIII isoform pattern which was observed in 4/80 children with acute lymphatic leukaemia (ALL) and in 1/4 children with Ewing's sarcoma, has been shown by family studies to be due to a mutant form of ATIII (AT Dublin) in the heterozygous state. The coagulation properties of AT Dublin heterozygotes were normal. In addition the immunological and activity levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Plasma protease C1 inhibitor (SERPING1), antithrombin III, and fibronectin were found to play a role in carcinogenesis, but their implication in oral cancer, especially in OSCC, has not been demonstrated yet . The CFH was previously identified in lung adenocarcinoma and cutaneous squamous cell carcinoma, but not in OSCC , and apoB100 was found in serum of patients with head and neck squamous cell carcinoma .…”
Section: Resultsmentioning
confidence: 99%
“…Plasma protease C1 inhibitor (SERPING1), antithrombin III, and fibronectin were found to play a role in carcinogenesis, but their implication in oral cancer, especially in OSCC, has not been demonstrated yet . The CFH was previously identified in lung adenocarcinoma and cutaneous squamous cell carcinoma, but not in OSCC , and apoB100 was found in serum of patients with head and neck squamous cell carcinoma .…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing of SERPINC1 encoding antithrombin subsequently revealed a single nucleotide variation predicting a p.Val30Glu substitution in the signal peptide of antithrombin which redirects signal peptidase cleavage to a site two amino acids into the mature protein and results in removal of the N-terminal dipeptide from antithrombin (3). Of note, while none of the heterozygous carriers of the Dublin variant identified in the original study had a history of thrombosis at the time of investigation, in our subsequent study we reported the Dublin variant in a patient with a history of spontaneous deep vein thrombosis and pulmonary embolus at age 41 and the presence of anti-IIa and anti-Xa activity levels at the lower end of the normal range (2,3). Its variable association with thrombosis and the observation that the Dublin variant, denoted rs2227624, is relatively prevalent in the European population (MAF 0.0017 in the ExAC database (http://exac.broadinstitute.org/variant/1-173884010-A-T) have meant that its clinical significance has remained elusive.…”
Section: Dear Sirsmentioning
confidence: 75%
“…Antithrombin Dublin was first described by one of us in 1987 when it was identified as part of a study that aimed to determine the effects of asparaginase therapy on the different plasma isoforms of antithrombin that can be distinguished by isoelectric focusing. The Dublin variant was found to be more negatively charged when compared with normal antithrombin (2). Sequencing of SERPINC1 encoding antithrombin subsequently revealed a single nucleotide variation predicting a p.Val30Glu substitution in the signal peptide of antithrombin which redirects signal peptidase cleavage to a site two amino acids into the mature protein and results in removal of the N-terminal dipeptide from antithrombin (3).…”
Section: Dear Sirsmentioning
confidence: 99%
“…2). Of all the 15 genes, 8 and 4 have been reported to be differentially expressed in HCC10, 11, 13, 22–26 and other types of cancers,27, 28, 29, 30, 31, 32, 33 respectively. There were 3 genes first identified to be lowly expressed in HCC in our present study (Table IV).…”
Section: Resultsmentioning
confidence: 99%